Low-cost synchronization of high-speed audio and video recordings in bio-acoustic experiments - Laurijssen, D.; Verreycken, E.; Geipel, I.; Daems, W.; Peremans, H.; Steckel, J. (The Journal of Experimental Biology, 2018)
In this paper, we present a method for synchronizing high-speed audio and video recordings of bio-acoustic experiments. By embedding a random signal into the recorded video and audio data, robust synchronization of a diverse set of sensor streams can be performed without the need to keep detailed records. The synchronization can be performed using recording devices without dedicated synchronization inputs. We demonstrate the efficacy of the approach in two sets of experiments: behavioral experiments on different species of echolocating bats and the recordings of field crickets. We present the general operating principle of the synchronization method, discuss its synchronization strength and provide insights into how to construct such a device using off-the-shelf components.